"Give Me Sight Beyond Sight": Thinking With Science Fiction as Thinking (Together) With (Others). (February 2016) - Stingl, Alexander I.
This is the second of two special issues, and the articles are grouped according to two themes: The previous, first issue featured articles that shared the theme Technologies and the Political, while this second issue is focused on the theme of Subjectivities . In this second, somewhat expanded, introduction, the "sky's the limit." This introduction canvasses various theoretical and conceptual-empricial perspectives that the articles of both issues touch on and further tries to open many doors through which readers are invited to go on their own rather than give readymade answers. This introduction is written not only to give both an overview of some of the most important conceptual, methodological, and empirical contexts that the two special issues evoke but also to create invitations for many further conversations to be had from here on forward by beginning the interrogating and troubling of the intercourse between "science" and "science fiction": beause all of this has happened before and will happen again.